USE of Rice Husk Ash (RHA), Marble Dust (MD) and LIME in Bricks with Variations in its Percentage of Composition - Adhav Prashant; Nandkhile Gaurav; Nimbalkar Abhijit; Pachpute Swapnil; Pawar Ashitosh; Prof. Khamkar R. S; Prof. Pachpute A. B (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Strong Material is a key factor in measuring strength of a Structure. The fact that India is a developing nation having Mega structure and line up in the strongest nations of the world. For strong structure strength of material used should be high enough. What if the concrete used is having a high strength and we are also able to save the material and make it eco Friendly. That’s the better idea to make the structure ecofriendly and also the use of material is less? Bricks that available in some regions have poor quality, low compressive strength, higher water absorption and uneven surfaces Therefore in this study, rice husk ash has been utilized for the preparation of bricks in partial replacement of clay. The main objective of the project is to expedite the improvement of infrastructure with the help of High-Performance Concrete. The project has one of the major advantages that we can use the waste material produced during farming and use that thing in the improvement of strength of material and use it in the construction part of mega structures.
Keywords: High-Performance Concrete; High-Performance ConcreteHigh-Performance Concrete